Dinamika Stres Pengasuhan Pada Orangtua dengan Anak Bibir Sumbing - Koamesah, Grace Tesabela; Ongkowidjojo, Olivia; Alvianto, Dino (Psychopreneur Journal, 2021)
This study aims to explore the dynamics of parenting stress experienced by parents with cleft children. Previous studies were conducted with quantitative methods. therefor a qualitative approach is used to better understand the dynamics of parenting stress through parents' perspective. Purposive sampling is used with the help of NGO who facilitate families with cleft children. The data is analyzed with thematic analysis and cross-case comparison. Result shows that parenting stress began with a stressor, which is the fact that parents had clef children. Parents then showed emotional and behavioral responses which potentially trigger parenting stress influenced by risk and protective factors. Existing risk factors could predict a higher level of parenting stress, meanwhile protective factors are able to reduce the level of parenting stress. This study further finds that mixed emotion could appear as an emotional response, also that religious value played an important role as a protective factor.